Template-assisted humidity sensors based on PFO-DBT nanotubes: Fabrication and characterization - Fakir, Muhamad Saipul (Springer, 2022)
In this study, capacitive humidity sensors based on grown poly2,7-(9,9-dioctylfluorene)-alt-4,7-bis(thiophen-2-yl)benzo-2,1,3-t hiadiazole] (PFO-DBT) nanotubes and anodic aluminum oxide (AAO) template is fabricated and characterized. The active layer of the device consists of infiltrated PFO-DBT solution on AAO template, thereby growing the PFO-DBT nanotubes. Infiltration was performed by three different deposition methods, namely spin coating, immersion of AAO template in polymeric solution and deposition by vortex mixer. Results showed that each method yielded a large-scale production of PFO-DBT nanotubes with different specifications. The open-end of the PFO-DBT nanotubes at the top surface of the template acts as porous, which provides a larger sensing area for device, thus enhancing the performance of the device. Furthermore, the infiltrated PFO-DBT in the porous has significantly increased the sensitivity of the device compared to that of the used empty AAO template. The impact of distinct morphology of the structure on the electrical properties such as device sensitivity, hysteresis and its respond and recovery time are also investigated and elaborated.